The first and oldest record of Issidae from the Lower Cretaceous of Lebanon (Hemiptera, Fulgoromorpha) - Azar, Dany; Maksoud, Sibelle; Robin, Ninon; Godefroit, Pascal; Cavin, Lionel; Olive, Sébastien; Rey, Kévin; Vallée-Gillette, Nathan; Brito, Léa De; Heneine, Geryes; Nel, André (Zootaxa, 2024)
Libanissus bkassinensis Azar, Maksoud & Nel, gen. et sp. nov. is illustrated and described from the Lower Cretaceous dysodile (oil papershales) of Bkassine, South Lebanon, and its taxonomic position discussed. Libanissus bkassinensis Azar, Maksoud & Nel, gen. et sp. nov. is characterized by its banded legs and body, a hind wing with two lobes, RA and RP very short, M with only two very short apical branches, CuA with two branches, and a small but distinct apical furcation of PCu close to the incision of the wing margin. Libanissus bkassinensis Azar, Maksoud & Nel, gen. et sp. nov. represents the earliest record (lower Barremian) of the Issidae. Prior to this discovery, the oldest known record was from the Paleocene of France.